IMPLEMENTASI APLIKASI BERBASIS WEB UNTUK PEMESANAN DONAT DAN MENENTUKAN PEMILIHAN TOPING DONAT PADA TOKO ANHARI MENGGUNAKAN METODE AGILE DAN ALGORITMA ASSOCIATION RULE MINING - Moh. Yusuf Hidayattuloh; Akrom Akrom (LPPM Politeknik Pratama Kendal, 2026)
Anhari Donut Shop still uses a manual ordering system, resulting in frequent recording errors and difficulties in analyzing customer purchasing patterns. This research aims to design a web-based application system for donut ordering while providing topping recommendations based on transaction history. The development method used is Agile, while pattern analysis was performed using the Association Rule Mining (Apriori) algorithm. The developed system is capable of managing customer and transaction data and generating association rules as the basis for topping recommendations. Black Box testing results indicate that all features function as required. Thus, the system can improve ordering effectiveness and support data-driven decision-making.